Reactive arthritis following Mycobacterium tuberculosis infection in a post-renal transplant patient (1994)
Reactive arthritis following infection with mycobacterial tuberculosis was first described by Poncet at the end of the last century. Since then, there has been a limited number of cases reported in the literature and many authors question its authenticity. The presence of oligo or polyarticular synovitis without suppuration or caseation after Mycobacterium tuberculosis infection (TB), has been noted. We describe one patient with Poncet's arthritis following renal transplant.